2014
DOI: 10.1017/sjp.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Overt and Subtle Discrimination, Subjective Well-Being and Physical Health-Related Quality Of Life in an Obese Sample

Abstract: Obesity represents a serious health issue affecting millions of people in Western industrialized countries. The severity of the medical problems it causes is paralleled by the fact that obesity has become a social stigma that affects the psychological health-related quality of life of individuals with weight problems. Our study, with 111 obese patients of a Spanish hospital, focused specifically on how overt and subtle discrimination is related to subjective well-being (affect balance and life satisfaction) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…Self-stigma was low-to-moderate in this sample, paralleling previous findings on perceived personal discrimination among Spanish individuals with obesity [10,11,22,23,47]. Women demonstrated higher weight-related self-stigma compared to men; as others have indicated, women are more affected by weight stigmatization [7] and group discrimination [23], yet this finding has not been previously found among Spanish individuals with obesity seeking or undergoing treatment for weight loss [10,11,23,47]. While others have not found an influence of BMI on stigma among individuals with excess weight [10,11,23], some research exists on the positive relationship between weight and weight self-stigma [47], and we found that participants with obesity showed marginally higher self-stigma compared to individuals with overweight.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Self-stigma was low-to-moderate in this sample, paralleling previous findings on perceived personal discrimination among Spanish individuals with obesity [10,11,22,23,47]. Women demonstrated higher weight-related self-stigma compared to men; as others have indicated, women are more affected by weight stigmatization [7] and group discrimination [23], yet this finding has not been previously found among Spanish individuals with obesity seeking or undergoing treatment for weight loss [10,11,23,47]. While others have not found an influence of BMI on stigma among individuals with excess weight [10,11,23], some research exists on the positive relationship between weight and weight self-stigma [47], and we found that participants with obesity showed marginally higher self-stigma compared to individuals with overweight.…”
Section: Discussionsupporting
confidence: 86%
“…Self-stigma was low-to-moderate in this sample, paralleling previous findings on perceived personal discrimination among Spanish individuals with obesity [10,11,22,23,47]. Women demonstrated higher weight-related self-stigma compared to men; as others have indicated, women are more affected by weight stigmatization [7] and group discrimination [23], yet this finding has not been previously found among Spanish individuals with obesity seeking or undergoing treatment for weight loss [10,11,23,47].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A covariation of both was found with those with high rates of psychological well-being reporting beter health-related quality of life compared to those who reported a moderate sense of psychological well-being [30]. It has been recently found that a person's subjective perception of their own well-being greatly inluences HRQL, suggesting that by increasing people's perceptions we can help them atain higher levels of health-related quality of life [31], as well as beter quality of life during childhood and adolescence [32].…”
Section: Theoretical Frameworkmentioning
confidence: 91%